Seasonal litterfall dynamics in pine and oak forests of central forest steppe - Sheshnitsan Tatiana; Sheshnitsan Sergey (BIO Web of Conferences)
The study of litterfall dynamics is of particular relevance in the forest-steppe zone, where forest ecosystems are characterized by high variability of climatic conditions and soil characteristics. The aim of this study was to analyze the seasonal dynamics of litterfall in pine and oak forests. Litterfall was collected during the seasonal maximum input period, from August to November, and then subjected to laboratory fractionation and carbon content determination. The results demonstrated significant differences in the dynamics and magnitude of litterfall input between pine and oak forests. Maximum litterfall (69 g/m²) in pine forests was reached in October and was composed primarily of needles (59%) and branches/bark (28%), and in oak forests – 166 g/m2. The carbon content of the different litterfall fractions was found to be higher in pine forests than in oak forests. Seasonal carbon flux with litterfall was estimated to be 0.62 MgC/ha in pine forests and 1.12 MgC/ha in oak forests. The observed differences in the dynamics and carbon content of litterfall between two types of forests can be attributed to the biochemical and phenological differences between coniferous and deciduous trees. The findings are significant for the development of strategies for the sustainable management of forest ecosystems in the context of climate change.